(untitled) (International Journal of Mathematics and Physics, 2016)
This paper presents numerical simulations of the water flow in the case of an emergency at the protective hydraulic engineering constructions. A mathematical modelfor simulation of water flow is based on Navier-Stokes equations derived from the conservation mass law and with phase equation. Numerical discretization of system of equations is done by finite volume method. System of water flow is solved by projection method. The phase and momentum equations are solved by Runge-Kutta method, and for the solution of Poisson equation the Jacobi method is applied. A program code was developed in C++ for numerical realization of water flow at emergency at the protective hydraulic engineering constructions.Numerical results are illustrated by figures. G M T Английский Испанский Итальянский Казахский Китайский Трад Китайский Упр Корейский Русский Турецкий Французский Английский Испанский Итальянский Казахский Китайский Трад Китайский Упр Корейский Русский Турецкий Французский Звуковая функция ограничена 200 символами Настройки : История : Обратная связь : Donate Закрыть